2020
DOI: 10.3390/cancers12040818
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Macrophages Act in Concert Towards a Beneficial Outcome in Colon Cancer

Abstract: In colon cancer, the prognostic value of macrophages is controversial, and it is still unknown how hypoxia modulates macrophage–cancer cell crosstalk. To unravel this, co-cultures of human primary macrophages and colon cancer cells were performed at 20% and 1% O2, followed by characterization of both cellular components. Different colon cancer patient cohorts were analyzed for hypoxia and immune markers, and their association with patient overall survival was established. A positive correlation between HIF1A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There are few in-vitro studies in tumors using hypoxic condition to investigate the effects of LA or tumor-conditioned media on the macrophage polarization. In a recent study of colon cancer by Martins et al [41], they co-cultured human primary macrophages with colon cancer cells under 20% (normoxia) and 1% (hypoxia) O2, and found that hypoxia drived macrophages into a M1-phenotype. Their results support our findings that normoxia and hypoxia have different effects on the polarization of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…There are few in-vitro studies in tumors using hypoxic condition to investigate the effects of LA or tumor-conditioned media on the macrophage polarization. In a recent study of colon cancer by Martins et al [41], they co-cultured human primary macrophages with colon cancer cells under 20% (normoxia) and 1% (hypoxia) O2, and found that hypoxia drived macrophages into a M1-phenotype. Their results support our findings that normoxia and hypoxia have different effects on the polarization of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoxia may have beneficial effects on cancer therapy via SIRPα-CD47 axis. Colon cancer has a better prognosis than other cancer types because it has higher levels of macrophage infiltration and HIF-1α expression [ 104 ]. Hypoxia can decrease SIRPα expression in macrophages while simultaneously increasing CD47 expression in colon cancer cells.…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%
“…Hypoxia can decrease SIRPα expression in macrophages while simultaneously increasing CD47 expression in colon cancer cells. The heightened signal of "don't eat me" is countered by the reduced SIRP expression level, increasing the phagocytic capacity of macrophages [ 104 ]. Therefore, HIF-1α does have the ability to enhance phagocytosis of macrophages, which may be dependent on cancer types [ 158 ].…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%
“…The development of cell-based immunotherapy can be achieved by establishing cell lines that express tumor selectivity and cytotoxic functions. Several prospective candidates that have been rigorously studied are natural killer (NK) cells, dendritic cells (DC), macrophages and T-lymphocytes [ 13 , 14 , 15 , 16 ]. These cells play critical roles in alerting the immune system (e.g., chemotaxis), arming other immune cells (e.g., antibody-dependent and cytokine-dependent activation) and exerting their cytotoxic effect against the cancer cells (e.g., receptor-mediated cell apoptosis).…”
Section: Introductionmentioning
confidence: 99%